Arabia a journey through the heart of the Middle East - Wood, Levison (Hodder &​ Stoughton, 2018)
Following in the footsteps of great explorers such as Lawrence of Arabia and Wilfred Thesiger, Arabia is Levison Wood's account of his most complex expedition yet: circumnavigating the Arabian Peninsula. Travelling through some of the harshest and most beautiful environments on earth, he seeks to challenge our perceptions of an often misunderstood part of the world, seeing how the region has changed and examining the stories we don't often hear about in the media.